الإدارة الإلكترونية لمصالح مسح الأراضي والحفظ العقاري - بوهلال, أحمد عمار; مختارة, عبد الجليل; حسينــــي, الصادق (University of Eloued جامعة الوادي, 2023)
من خلال موضوع بحثنا تحت عنوان الإدارة الإلكترونية في مصالح مسح الأ ا رضي والحفظ العقاري قمنا بتقسيمو إلى فصمين ميمين، تطرقنا في الفصل الأول إلى الإدارة الإلكترونية في مصالح مسح الأ ا رضي والحفظ العقاري قبل الدمج، تناولنا فيو إلى بداية إنشاء مسح الأ ا رضي من خلال الوكالة الوطنية لمسح الأ ا رضي وىيكميا التنظيمي، ثم م ا رحل تطبيق الب ا رمج الإلكترونية المساعدة في عممية المسح، إلى إنشاء إدارة الحفظ العقاري والمحافظات الولائية وىياكميا التنظيمية، و الب ا رمج المطبقة فييا، ثم دور كل من ىذه المصالح في تسيير العقار. مع التنويو إلى م ا زيا ىذه الب ا رمج وكذا عيوبيا، ومساىمتيا سمبا أو إيجابا في حل قضايا العقار العالقة. لنتطرق في الفصل الثاني إلى الإدارة الإلكترونية في مصالح مسح الأ ا رضي والحفظ العقاري بعد الدمج، منذ تاريخ الإعلان عن ىذا المشروع إلى حل الوكالة الوطنية لمسح الأ ا رضي ودمجيا مع مصالح الحفظ العقاري تحت وصاية الأملاك الوطنية، واليياكل الجديدة المنبثقة عن ىذا الدمج، تناولنا بالتفصيل إلى المشروع الأسمى الذي أولت لو المصالح العميا لمبلاد أىمية بالغة لمحد من مشاكل العقار وىو البرنامج الموحد للإدارتين – منصة العقار والع ا رقيل التي صادفت ولا ا زلت تصادف تطبيق ىذا مشروع عمى ارض - الواقع. لنخمص في الأخير إلى بعض الحمول والمقترحات التي يمكن إن تساىم في التطوير الأمثل ليذا المشروع، كحل امثل لتقريب الإدارة من المواطن، والقضاء تدريجيا عمى الصعوبات التي تؤرق المواطن والشريك الميني عمى حد سواء.Throughot (through) of or research topic which underlined of “Electronic governanece admin,stration”in survey and conservation land Services, we have divided it into two important chpters:in the firstchapter we talked about land Survey and Land conservation before the mrger, the etablishment of the Land Survey through the National land Survey Agency and its organizational structure at the beginning, then the implementation stages of electronic software assisting in the Survey process, to estab lish the department of Land Conservation, the State Governorates and their regulatory structure, in addition to the programmes applied there, then the role of each of these interests in the administration of the property. Noting that the advantages and disadvantages of these programs, and how it can be contributed positively or negatively in resolving outstanding property issues. The second chapter was about Land Survey and Land Conservation after the marger, from the date of announcement of this project to the dissolution of the National Land Survey Agency And its itegration with Land Conservation interests under the custody of national property and the new . Structures deriving from such intergration, we elaborated on the supreme project to which the cou Countrys supreme interests attached great importance to reduce property problems, the unified programme of the two deartements_a real estate platform en countered obstacles continues to coin cide with the implementation of this project on the ground. Finally, we find some solutions and suggestions that can contributing to the optimal dev elopement of this projet, by making the administration more closely to the citizen as an ideal one and eliminate gradually the difficulties that effect on that effect on the both citizen and the professional partner.
مذكرة ماستر
Keywords: الإدارة الإلكترونية .دمج مصالح مسح الأ ا رضي و الحفظ العقاري; E-management. Integrate land survey and real estate conservation interests